Еврейский вопрос в политике модернизации позднеимперской России - Безаров, Олександр Троянович; Безаров, Олександр Троянович (Studia Żydowskie. Almanach, 2021)
The Jewish question in the politics of modernization of late Tsarist Russia The article analyzes the Jewish question in the modernization policy of the Tsarist government in the second half of the 19th – early 20th century. The author is convinced that the Jewish question (the question of Jewish equality) was a topical issue at all three stages of the modernization policy. Thus, if in the period of the Great Reforms the Jewish question was considered through the prism of the political loyalty of the Jews to the autocratic regime of Alexander II, who was inclined to grant them equality, then in the second and third stages (1881-1911) the problem of Russian Jews was exacerbated by the rise of state anti-Semitism, which was an integral part of the ideology of imperial nationalism. Some attempts to solve the Jewish question were made at the beginning of the 20th century in the policies of V. K. Pleve, V. N. Kokovtsev, S. J. Witte, and P. A. Stolypin. However, against the background of the contradiction of the tsarist state policy towards the Jewish question in general and in the modernization period in particular, the hopes of Russian Jews for emancipation disappeared. Conclusions were drawn that the modernization policy was essentially inorganic, which could not fail to be reflected in ideological and political approaches to the Jewish question. Despite some concessions, such as granting equal rights to Jews in the Kingdom of Poland in 1862, to Russian Jews the right to vote in 1905-1907, and attempts to abolish quota system for Jewish academicians in 1907-1908, the government did not dare to abolish the institution of the Jewish settlement zone, which was essentially a form of medieval ghetto. The policy of state anti-Semitism was not only a result of the Romanovs' strengthening of tsarist patriotism and religious mysticism, but also a reaction of the autocracy to the noticeable political and revolutionary activities of the Jews. According to the author, the autocracy of the last Romanovs proved to be hostage to its own modernization policy. The country was preparing for deep revolutionary changes, in which the Jewish question played an important role.
Еврейский вопрос в политике модернизации позднеимперской России
Keywords: єврейське питання, Російська імперія, модернізація